ANALYSIS OF THE MACRO- AND MICROELEMENTS IN THE ABOVE-GROUND PART OF PAPAVER PAVONINUM (Scientific journal of the Fergana State University, 2025)
The moisture content of the dried above-ground part of the Papaver pavoninum plant was determined by drying in a drying oven. The ash content was established by heating the plant material in a muffle furnace. The macro and microelement composition of the plant ash was studied using a high-efficiency energy-dispersive X-ray fluorescent spectrometer.